SERVICE QUALITY AND CUSTOMER INTIMACY IN DRIVING DONOR LOYALTY: THE MEDIATING ROLE OF DONOR SATISFACTION IN ISLAMIC PHILANTHROPY - Senidin Senidin; Djawoto Djawoto; Bambang Hadi Santoso (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to examine the effect of service quality and customer intimacy on donor loyalty, with donor satisfaction as a mediating variable, at LAZNAS BMH Surabaya. The research adopts a quantitative approach using Partial Least Square Structural Equation Modeling (PLS-SEM) and involves 376 active donors as respondents. The results indicate that service quality and customer intimacy have significant positive effects on donor satisfaction and donor loyalty. Customer intimacy shows a stronger direct influence on donor loyalty compared to service quality. Furthermore, donor satisfaction significantly affects donor loyalty and serves as a partial mediating variable in the relationship between service quality and customer intimacy with donor loyalty. The findings highlight that donor loyalty in Islamic philanthropic institutions is not only driven by service performance but also by relational engagement and satisfaction. Therefore, integrating service excellence with relationship-based strategies is essential to enhance donor loyalty and ensure long-term sustainability. This study contributes to the literature by providing empirical evidence on donor behavior within the context of Islamic philanthropy and offers practical insights for improving donor relationship management.